2017
DOI: 10.1177/0898264317730487
|View full text |Cite
|
Sign up to set email alerts
|

Life-Space Predicts Health Care Utilization in Community-Dwelling Older Adults

Abstract: Life-space is a practical alternative in predicting future health care utilization to performance-based measures, which can be difficult to incorporate into clinical or public health practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Kennedy et al 19 sought to determine whether decline in LSA predicts increased health care utilization among participants in the UAB Study of Aging. The authors found that a 10-point decrease in life-space was associated with 14% increased odds of an emergency department visit and/or hospitalization over the next month, after controlling for all covariates.…”
Section: Resultsmentioning
confidence: 99%
“…Kennedy et al 19 sought to determine whether decline in LSA predicts increased health care utilization among participants in the UAB Study of Aging. The authors found that a 10-point decrease in life-space was associated with 14% increased odds of an emergency department visit and/or hospitalization over the next month, after controlling for all covariates.…”
Section: Resultsmentioning
confidence: 99%
“…Life-space mobility represented an essential aspect of environmental complexity in older adults (42). Despite not being a direct measure of physical performance, LSA has been described as a comprehensive representation of functioning and a strong predictor of adverse outcomes in older age, including falls, cognitive decline, hospitalization, institutionalization, and death (42)(43)(44)(45)(46). While physical performance (such as walking ability) accounts for a significant portion of its final score, LSA is strongly associated with several other factors that influence mobility, including social connections, cognitive performance, personality traits, and mental health (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Lo et al described a significant correlation between LSM and incident falls on multivariate analysis during 6-month follow-up from the UAB Study of Ageing (OR for each ten-point decrement in life space = 1.16, 95% CI 1.03–1.31, P = 0.02) [ 48 ]. Follow-up at 36 months found an association between a decline in UAB LSA score and healthcare utilisation (as measured by self-reported ED visits and hospitalisation episodes) [ 49 ].…”
Section: Associations Between Lsm and Other Outcomesmentioning
confidence: 99%